The Use of the Computer in the Cancer Registry - Parkin, D. M.; Demaret, Eva; Crosignani, P. C. (Methods of Information in Medicine, 1983)
A survey of the members of the International Association of Cancer Registries was carried out to determine the extent to which their registry procedures had been automated by the use of computers. The great majority of these registries were population-based, and most (73%) had access to a computer, the exceptions being registries in developing countries. Computerised registries were larger in size than manual ones and had higher levels of staffing. Questions on recent changes to registry systems revealed a trend to increasing availability of direct on-line access to the computer master file and the use of data-base management systems. The low cost of suitable computers and software packages means that inexpensive automated systems will probably soon be within reach of all but the smallest registries.
Keywords: Cancer; Data Base; Data Processing; Medical Computer Applications; Register